Why can Mozambique Tilapia Acclimate to Both Freshwater and Seawater? Insights From the Plasticity of Ionocyte Functions in the Euryhaline Teleost - Inokuchi, Mayu; Hiroi, Junya; Kaneko, Toyoji (Frontiers in Physiology, 2022)
In teleost fishes, ionocytes in the gills are important osmoregulatory sites in maintaining ionic balance. During the embryonic stages before the formation of the gills, ionocytes are located in the yolk-sac membrane and body skin. In Mozambique tilapia embryos, quintuple-color immunofluorescence staining allowed us to classify ionocytes into four types: type I, showing only basolateral Na+/K+-ATPase (NKA) staining; type II, basolateral NKA and apical Na+, Cl− cotransporter 2; type III, basolateral NKA, basolateral Na+, K+, 2Cl− cotransporter 1a (NKCC1a) and apical Na+/H+ exchanger 3; and type IV, basolateral NKA, basolateral NKCC1a and apical cystic fibrosis transmembrane conductance regulator Cl− channel. The ionocyte population consisted mostly of type I, type II and type III in freshwater, while type I and IV dominated in seawater. In adult tilapia, dual observations of whole-mount immunocytochemistry and scanning electron microscopy showed morphofunctional alterations in ionocytes. After transfer from freshwater to seawater, while type-II ionocytes closed their apical openings to suspend ion absorption, type-III ionocytes with a concave surface were transformed into type IV with a pit via a transitory surface. The proposed model of functional classification of ionocytes can account not only for ion uptake in FW and ion secretion in SW, but also for plasticity in ion-transporting functions of ionocytes in tilapia.